The Green Fields of Ireland: The Legacy of Dublin's Housing Boom and the Impact on Commuting - CAULFIELD, BRIAN (My University, 2014)
Dublin, like many other international cities has experienced a significant housing boom in the past decade. This boom has seen an unprecedented increase in the numbers of houses built and in the density of housing at the periphery of the city. In addition, Dublin has become a more dispersed city with centres of employment no longer being focussed only in the Central Business District (CBD). At the same time, the provision of public transport infrastructure, while it has improved, has not kept pace with the increase in housing stock, leading to high levels of car dependency in these peripheral suburban areas. This paper seeks to examine how commuting patterns have changed as a result of this increasing in housing stock. The results presented in this paper shows that even within the same electoral districts, commuters living in housing built after 2001 are more likely to drive than those living in older housing. This paper analyses the modal choices of commuters living in both new and older housing and describes the factors that may be leading to higher levels of car dependency in those living in newer housing. The case study presented in this paper shows a city region in transition and documents the impact that a housing boom has had upon commuting patterns.
PUBLISHED
Keywords: Housing Urban sprawl; Smart & Sustainable Planet